2016
DOI: 10.4103/2279-042x.185728
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to stress-related mucosal damage prophylaxis guideline in patients admitted to the Intensive Care Unit

Abstract: Objective:Concern about adverse effects of the inconsistent use of stress-related mucosal damage prophylaxis in intensive care unit (ICU) is increasing. Hence, this study was designed to prospectively evaluate the rate of inappropriate stress ulcer prophylaxis (SUP) administration upon ICU admission, at ICU discharge and determine the adherence to American Society of Health-System Pharmacists (ASHP) guideline during ICU stay.Methods:In this study, 200 patients were randomly selected from all ICU admissions dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
1
5
0
1
Order By: Relevance
“…In most of the medical records reviewed (97.6%), the patients were on peptic ulcer prophylaxis. This finding demonstrates an improvement on previous studies in ICUs, which reported 53e78% compliance with peptic ulcer prophylaxis in similar populations [35,37]. The results of this study are consistent with the Surviving Sepsis Campaign guidelines, which strongly recommend peptic ulcer prophylaxis in mechanically ventilated patients [38,39].…”
Section: Discussionsupporting
confidence: 88%
“…In most of the medical records reviewed (97.6%), the patients were on peptic ulcer prophylaxis. This finding demonstrates an improvement on previous studies in ICUs, which reported 53e78% compliance with peptic ulcer prophylaxis in similar populations [35,37]. The results of this study are consistent with the Surviving Sepsis Campaign guidelines, which strongly recommend peptic ulcer prophylaxis in mechanically ventilated patients [38,39].…”
Section: Discussionsupporting
confidence: 88%
“…Recently, Rafinazari et al studied the use of SUP during ICU stay and found that 80% patients received SUP, in which 44.4% showed no indication according to the AHSP guidelines; while 6.3% did not receive SUP though it was indicated. 18 In 2015, Krag et al found that 73% ICU patients received SUP and 59% patients with clinically important GI bleed had received SUP prior to bleed. 13 Krag et al found that CSGIB was associated with use of SUP on day 1 but not with mechanical ventilation.…”
Section: Resultsmentioning
confidence: 99%
“…1 Rafinazari et al also reported that, in their study, 38.5% of patients did not receive appropriate SUP on ICU admission and 81.2% continued on inappropriate SUP upon transfer from ICU. 18 Wohlt et al reported that 394 patients met the eligibility criteria for SUP, 357 patients were prescribed SUP, and 80% continued SUP on transfer from ICU. 27 This also imposes an unnecessary financial burden and increases the cost of healthcare.…”
Section: Resultsmentioning
confidence: 99%
“…Bu amaçla farklı seçenekler olmakla birlikte, ideal strateji tartışmalıdır. En önemli stratejinin erken enteral beslenme olduğu vurgulanmakla birlikte, farmakolojik ajan olarak proton pompa inhibitörleri ya da H2 reseptör blokerleri en sık tercih edilen ajanlardır (16)(17)(18)(19)(20) .…”
Section: Sedation (Sedasyon)unclassified